Data from: The significance of retention trees for survival of ectomycorrhizal fungi in clear‐cut Scots pine forests ... - Sterkenburg, Erica; Clemmensen, Karina E.; Lindahl, Björn D.; Dahlberg, Anders (Dryad, 2019)
1. Forestry with short stand generations and simplified forest structures has markedly af-fected forest biodiversity. One group of organisms adversely affected by clear-cutting is ectomycorrhizal (ECM) fungi, as they are associated with the roots of living trees. Retention forestry is a way of reducing logging impacts and enhancing biodiversity conservation. In-creasing the proportion of trees retained at harvest may improve ECM fungal diversity. 2. We investigated the potential for life-boating of ECM fungi through the harvesting phase in an experimental field study in a 190 years old Scots pine forest in northern Sweden. The experiment comprised four levels of tree retention – unlogged forest, plots with 60% or 30% of evenly distributed trees retained, and clear-cuts without retained trees. We sampled soils and determined identities, frequencies and relative abundances of ECM fungal species dur-ing three years following logging through the use of high-throughput sequencing of ampli-fied ITS2 markers. 3. We ... : Appendix Table 1-6Six appenix tables;Table 1. Number of naturally established Scots pine seedlings; Table 2. Taxonomic affiliations, species name, reference sequecences and no of times detected in the plots; Table 3. Significant parameters in a linear mixed model of the relative abundance of ectomycorrhizal (ECM) fungi; Table 4. Significant parameters in the linear mixed model of ECM fungal species richness; Table 5. No of reads (amplicons) of ECM fungal species pooled samples 2009-2013; Table 6. Number of Species Hypothesis and percentage of the total number of ECM fungal reads, for the most species rich genera and the order Thelephorales. ...